2020
DOI: 10.1175/mwr-d-19-0345.1
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation of the Convective Area and Eye Size Associated with the Rapid Intensification of Tropical Cyclones

Abstract: This study examines the diurnal variation of the convective area and eye size of thirty rapidly intensifying tropical cyclones (RI TCs) that occurred in the western North Pacific from 2015 to 2017 utilizing Himawari-8 satellite imagery. The convective area can be divided into the active convective area (ACA), mixed-phase, and inactive convective area (IACA) based on specific thresholds of brightness temperature. In general, ACA tends to develop vigorously from late afternoon to early next morning, while mixed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 69 publications
1
28
0
Order By: Relevance
“…Ocean feedback would be one of the essential components for TC intensity forecasts. Previous studies demonstrated that when the storm passes over a cold‐core eddy region or low ocean heat content area, TC intensity could be weakened depending on the TC translation speed (Lee et al., 2020; Lin et al., 2009; Ma, 2020). Figure 6 shows the number of convective cells and 36‐h integrated 10‐m atmospheric wind and 2‐m ocean current.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ocean feedback would be one of the essential components for TC intensity forecasts. Previous studies demonstrated that when the storm passes over a cold‐core eddy region or low ocean heat content area, TC intensity could be weakened depending on the TC translation speed (Lee et al., 2020; Lin et al., 2009; Ma, 2020). Figure 6 shows the number of convective cells and 36‐h integrated 10‐m atmospheric wind and 2‐m ocean current.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the lower OLR is typically coincident with deep convective areas. Figure 8 depicts the IRWVln (Lee et al., 2020) and simulated OLR at 1200 UTC 21 October. As shown in the IRWVln field, Typhoon Lan had a distinct eye and concentric eyewall structure (Figure 8a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations